2022
DOI: 10.3390/metabo12050383
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Metabolites in Gestational Diabetes Mellitus: A Narrative Review

Abstract: Gestational diabetes mellitus (GDM) is a major public health issue of our century due to its increasing prevalence, affecting 5% to 20% of all pregnancies. The pathogenesis of GDM has not been completely elucidated to date. Increasing evidence suggests the association of environmental factors with genetic and epigenetic factors in the development of GDM. So far, several metabolomics studies have investigated metabolic disruptions associated with GDM. The aim of this review is to highlight the usefulness of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…The pathophysiology of GDM is still not entirely clear and it is the leading cause of endocrinopathy for pregnant women, complicating both maternal and fetal outcomes. 28 Furthermore, the prevalence is increasing (5%-20%) worldwide, accordingly, the importance of GDM screening is becoming more crucial in predicting and evaluating co-morbidities 4 Macrosomia, shoulder dystocia, large for gestational age, small for gestational age, cesarean delivery, preterm birth, respiratory distress syndrome (RDS), hypoglycemia, hypocalcemia, hyperbilirubinemia, and congenital anomalies are the some of the medical problems that the neonate of a pregnant woman with GDM may experience 29 comorbidities, developing T2DM is a known risk for patients with a history of GDM, and they also have a two-fold increased risk for cardiovascular diseases. 30 In a study by Hussein et al, 31 a group that refused to undergo GDM scan (GCT or OGTT-any oral glucose taking) and a group that had GDM scan were evaluated in terms of perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of GDM is still not entirely clear and it is the leading cause of endocrinopathy for pregnant women, complicating both maternal and fetal outcomes. 28 Furthermore, the prevalence is increasing (5%-20%) worldwide, accordingly, the importance of GDM screening is becoming more crucial in predicting and evaluating co-morbidities 4 Macrosomia, shoulder dystocia, large for gestational age, small for gestational age, cesarean delivery, preterm birth, respiratory distress syndrome (RDS), hypoglycemia, hypocalcemia, hyperbilirubinemia, and congenital anomalies are the some of the medical problems that the neonate of a pregnant woman with GDM may experience 29 comorbidities, developing T2DM is a known risk for patients with a history of GDM, and they also have a two-fold increased risk for cardiovascular diseases. 30 In a study by Hussein et al, 31 a group that refused to undergo GDM scan (GCT or OGTT-any oral glucose taking) and a group that had GDM scan were evaluated in terms of perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is one of the most important complications in pregnancy and its incidence is increasing every year all over the world. [2][3][4] It is known to be associated with increased risks of short-and long-term complications for both the pregnant woman and the fetus during pregnancy and postpartum. [5][6][7] Early intervention during pregnancy can significantly decrease the incidence of GDM risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes mellitus (GDM) is defined as the glucose tolerance that occurs or is determined for the first time during pregnancy in an individual with no preexisting diabetes 1 . It has been estimated to affect 5-20% of all pregnancies 2 . Although the pathophysiology of GDM has not yet been fully elucidated, it has been suggested that it causes low-grade systemic inflammation that exacerbates maternal immune responses 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiology of GDM has not yet been fully elucidated, it has been suggested that it causes low-grade systemic inflammation that exacerbates maternal immune responses 3 . As it leads to serious maternal and fetal complications if not monitored, it is of great importance that it should be screened during pregnancy and, if detected, should be appropriately followed up and treated 2 .…”
Section: Introductionmentioning
confidence: 99%